The faculty members' viewpoint about distance Exams during the Covid-19 Pandemic at Universities - Qasim Mohammed Hussein; Bassam Qasim Mohammed; Alaa K. Abbas; Nada Qasim Mohammed (Journal of Madenat Alelem University College, 2022)
This paper presents a field study on the scientific examinations integrity that conducted remotely for university students from teaching staff perspectives at Iraqi universities to identify the challenges and obstacles facing the E-exams for undergraduates and graduates education institutions. The paper aims supporting universities administrative to develop scientific and tractable solutions for conducting E-exams according to the available capabilities. For this purpose, a questionnaire was conducted, in which 805 instructors in public universities, most of them in scientific disciplines, participated in it. The questionnaire included (11) questions, the answer depends on multiple options. The questions were concerned on the extent of the scientific integrity of the E-exams that were carried out Covid-19.     The prominent results of our questionnaire were: 80% agreed that cheating occurred during on-line exams, and 74% agreed that  on-line exams did not distinguish between the non-glorified and the glorified student, 77% that the procedures of monitoring for electronic exams have no effect on cheating, 78% indicate that students have Groups in which questions are solved and distributed to the group during the exam, 91% have indications that   electronic exams scores were higher than the exams of on-sit.